Employability profiles of higher education graduates: a person-oriented approach - Monteiro, S. (2022)
Theoretical and empirical literature developed over recent years supports the concept of employability as a construct combining complex interactions of individual and contextual dimensions. This study aimed to identify differentiated profiles in graduates, combining personal and contextual variables related to employability. For this, 182 graduates from a public university were surveyed about their sociodemographic and educational pathways and employment status 18 months after university-to-work transition. Then, a latent class analysis was performed, which allowed the emergence of four distinct groups: well-equipped, high demand, vulnerable and non-traditional pathways. By adopting a person-centered approach, this study allowed the identification of different combinations of factors that, although recognized in current literature, seem to organize themselves differently among the heterogeneous population that presently obtain a higher education degree. This study also raises some practical implications, namely the importance of differentiated interventions, taking into consideration the specificities of each group.